Field-Testing Polyethylene Passive Samplers for the Detection of Neutral Polyfluorinated Alkyl Substances (PFASs) in Air and Water - Dixon-Anderson, Erik (Environ Toxicol Chem, 2018)
Fluorotelomer alcohols (FTOHs), perfluorooctane-sulfonamidoethanols (FOSEs), perfluorooctane-sulfonamides (FOSAs) and other poly- and perfluorinated alkyl substances (PFASs) are common and ubiquitous by-products of industrial telomerization processes. They can degrade into various perfluorinated carboxylic acids, which are persistent organic contaminants of concern. This study assessed the use of polyethylene (PE) passive samplers as a sampling tool for neutral PFAS precursors during field-deployments in air and water. A wide range of neutral PFASs was detected in PE sheets exposed in waste water treatment effluents in August 2017. Equilibration times for most neutral PFASs was on the order of 1–2 weeks. Based on known sampling rates, the partitioning constants between PE and water, K(PEw), were derived. Log K(pew) values were mostly in the range of 3 – 4.5, with greatest values for 8:2 FTOH, 10:2 FTOH and n-ethyl-FOSE. To test the utility of PE for gas-phase compounds, parallel active and passive sampling was performed in ambient air in Providence (RI, USA) in April 2016. Most PFASs equilibrated within 2–7 days. Greatest concentrations in PE samplers were detected for MeFOSE and EtFOSE. Polyethylene-air partitioning constants, log K(pEa), were ~ 7–8 for the FTOHs, and approached 9 for n-methyl-FOSA and n-methyl-FOSE. PE sheets showed promise as a passive sampling approach for neutral PFASs in air and water.